Data science in engineering and management applications, new developments, and future trends - Polkowski, Zdzislaw; Mishra, Sambit Kumar; Vasilev, Julian (CRC Press, 2022)
This book brings insight into data science and offers applications and implementation strategies. It includes current developments and future directions and covers the concept of data science along with its origins. It focuses on the mechanisms of extracting data along with classifications, architectural concepts, and business intelligence with predictive analysis. Data Science in Engineering and Management: Applications, New Developments, and Future Trends introduces the concept of data science, its use, and its origins, as well as presenting recent trends, highlighting future developments; discussing problems and offering solutions. It provides an overview of applications on data linked to engineering and management perspectives and also covers how data scientists, analysts, and program managers who are interested in productivity and improving their business can do so by incorporating a data science workflow effectively. This book is useful to researchers involved in data science and can be a reference for future research. It is also suitable as supporting material for undergraduate and graduate-level courses in related engineering disciplines.
Print version record
Keywords: Engineering -- Databases; Management -- Databases; Database management; Database searching; Bases de données; Gestion; Bases de données; Interrogation; online searching; Engineering; Management; Databases